PERMASALAHAN SEPUTAR HADIS MAUDHU’ - Novera, Melia (DIRAYAH : Jurnal Ilmu Hadis, 2022)
This research is a library research, and the data collected was analysed with descriptive approach. This study explains the problems surrounding the fake hadis or maudhu' hadis. Hadis maudhu 'is a lie that is made and engineered by someone and then attributed to the Prophet sallallaahu 'alaihi wa sallam. False hadis are as bad as weak hadis, even some scholars consider them a separate type outside of daif hadis. All scholars also agree that it is forbidden to narrate or convey the hadis maudhu 'except by explaining its essence, that it is a false hadis. However, this hadis has continued to circulate in the community so there needs to be education so that people know the law.